DOSIS DAN FREKUENSI KASCING UNTUK PENGENDALIAN PENYAKIT LAYU FUSARIUM PADA TANAMAN TOMAT - Susanna Susanna; Tjut Chamzurni; Arisandi Pratama (Jurnal Floratek, 2010)
A study of dosage and frequency of casting (earthwarm excrement) for controlling fusarium wilt disease (Fusarium oxysporum f.sp lycopersici) on tomatoes (Lycopersicum esculentum Mill) has been done in a Laboratory of Plant and Disease Department and a Field Experiment Station, Agriculture Faculty, Syiah Kuala University in Banda Aceh. The purpose of this experiment was to study effects of dosage and frequency of casting to control fusarium wilt on tomato plants. The experiment applied a factorial completely randomized design (CRD) with five replications. The factors studied were dosage and frequency of kascing. The dosage consisted of 100 and 200 g/plant, whereas the frequency of kascing consisted of one and two times of application. The results showed that dosage of 200 g/plant with two times of kascing application can control disease fusarium wilt on tomato plant.